Brand Positioning Analysis in Enhancing Customer Loyalty: A Systematic Literature Review - Prasetya, Feri Andika; Soetjipto, Budi Eko; Wardhana, Ludi Wishnu (PT. Maju Malaqbi Makkarana, 2025)
In an increasingly competitive business landscape, establishing a strong brand position is not merely an option but a necessity. Effective brand positioning not only helps brands differentiate themselves from competitors but also fosters a deeper emotional connection with customers. This study aims to analyze the relationship between brand positioning and customer loyalty using a Systematic Literature Review (SLR) approach. By reviewing previous research published in indexed journals, this study identifies key factors influencing the success of brand positioning, including product differentiation, customer perception, and brand communication consistency. The findings indicate that brands with a clear and consistent position in customers' minds are more likely to build long-term loyalty. Customers who feel connected to a brand’s values and identity are more inclined to remain loyal and even recommend the brand to others. Furthermore, this study reveals that the transition to the digital era has significantly altered how brands establish and maintain their position, with digital marketing strategies and message personalization emerging as critical factors in sustaining customer loyalty. This research underscores the importance of businesses not only in crafting a strong brand image but also in ensuring that customer experiences align with the brand’s promised values. By understanding and implementing effective brand positioning principles, companies can foster deeper and more sustainable relationships with their customers while enhancing their competitive edge in the market.